Efeitos agudos da press??o expirat??ria positiva na mobilidade toracoabdominal de pacientes com DPOC - Feitoza, Carla Lima (2016)
Introduction: Chronic obstructive pulmonary disease (COPD) is characterized by persistent obstruction that is usually progressive and associated with an inflammatory response in the airways and lungs, by harmful particles or gases. The thoracoabdominal mobility of COPD patients alters as a result of this obstructive process that causes permanent pulmonary hyperinflation, altering respiratory mechanics. As a result, physical efforts can increase minute ventilation by reducing the time to expiration, increasing this hyperinflation. Positive airway expiratory pressure (PEP) is a physiotherapeutic resource that helps reduce air trapping during exacerbations of the COPD patient, but little is known about the effects of PEP on pulmonary hyperinflation. As a rule, PEP with high pressures has been contraindicated. Objective: Evaluate the effects of physical effort and PEP on pulmonary hyperinflation and Thoracoabdominal mobility through optoeletronic plethysmography (OEP) in patients with COPD and in healthy individuals. Materials and Methods: Thoracoabdominal mobility was evaluated by OEP in 30 subjects, in two groups, 15 of them with GOLD (GDPOC) and 15 healthy subjects (GC), with a mean age of 58.1 ?? 11 years, before and after a daily life simulation activity, up and down the step and before and after performing a series of exercise with PEP. Results: Both the age and the anthropometric data of the studied population as weight and height showed no difference. The spirometric variables showed a significant difference, in favor of the CG, as expected. There were no significant differences in the contribution of the thoracoabdominal compartments at rest between groups, except for Ti / Tot in the GDPOC, with median of 0.77 characterizing possible hyperinflation or respiratory muscle fatigue. After physical exertion, for 2 minutes, the GDPOC group showed an increase in the Abd contribution in thoracoabdominal movements, higher than CG (52.2 ?? 12.6% vs. 41.1 ?? 14.6%). After PEP, there was an increase of abdominal compartment in the subjects of the GDPOC (50.5 ?? 19.1% x 36.9 ?? 16.4%). After the PEP the patients of the GDPOC had a normalization of Ti / Ttot, with a median of 0.41. As the analysis of the compartments in the GDPOC there is a greater involvement of the abdominal compartment in three moments evaluated and after PEP this abdominal participation is also greater than in the CG. Conclusion: Physical effort and the use of PEP alter the participation of thoracic and abdominal compartments differently between groups and PEP in COPD seems to contribute to the reduction of hyperinflation.